Internacjonalny charakter łacińskiej terminologii elektronicznej - Krukowska, Sylwia (Collectanea Philologica, 2015)
The article deals with the possibilities of the Latin language usage as a means of communication in the modern world. It is an analysis leading to answering the question about Latin’s inherent possibilities for passing the content, that so largely determinate the intellectual activity of modern man. Latin taking up this challenge requires introducing new terms and phrases to the resources of its vocabulary. The article discusses the currently used Latin international vocabulary in the field of electronics, computer science and the Internet, describing a number of issues concerning the lexical efficiency of Latin used these days. The aim of the study is to draw attention to the enormous potential that Latin possesses, and furthermore to demonstrate that due to its potential for word formation, Latin has a good chance to meet the challenges that the vast current technological progress and accordingly the requirement for creating new specialized terms pose for all languages.